Results of teaching foreign languages process informatization to future technical profile specialists - A. I. Mezentseva; A. G. Mikhaylova (Вестник Северо-Кавказского федерального университета)
The article deals with the issue of informatization of the process of training future technical specialists. Scientific works on the effectiveness of the use of electronic and multimedia learning tools are analyzed. The purpose of the article is to illustrate the practice of informatization of the process of training future technical specialists. Various means of informatization of the educational process are considered. The types of computer programs (KP) that are used in the process of training technical specialists are given. Some examples of the implementation of the software product «English: a short course of physics» in the educational process are presented. The conclusion is made that the software product allows to strengthen motivation and increase the interest of students in studying the discipline «Foreign language».